PROMOTING INVESTMENT ACTIVITY OF LARGE TAXPAYERS THROUGH TAX INCENTIVES - Tokhirov Shukhrat Niyoz ugli (American Journals, 2023)
The article is devoted to consideration of the efficient ways to promote investment activity of large taxpayers in our country. In addition, the article reveals the economic significance of the “tax incentive” concept. Relevant conclusions have been developed based on the analytical data on the tax incentives applied in our country by types of taxes.
Keywords: tax, tax incentive, investment, investment policy, investment operations, investment activity.